Solution:
Let's us suppose the cost of 1 hot dog is x and the cost of 1 potato chip is y.
![3x+3y=10.5 ------ Equation 1](https://img.qammunity.org/2019/formulas/mathematics/middle-school/h273x98s2yjhn6aoiv5xdzimfupsayf02s.png)
![2x+4y=9.5 ------- Equation 2](https://img.qammunity.org/2019/formulas/mathematics/middle-school/hagpwn46vxbwg0pzoucaw34dyymtvcp1cx.png)
Now if we multiply equation 1 by 2 and equation2 by 3, and subtract equation 1 from second we have:
Equation 1 will become :
6x+6y=21
Equation 2 will become:
6x+12y=28.5
Now subtracting above two, we have:
6x+12y=28.5
6x+6y=21
6y=7.5
y=1.25
Now lets us substitute the value of y=1.25 in equation 1:
then we have:
3x+3(1.25)=10.5
x=2.25
Therefore the cost of a hot dog is $2.25